RADI-22. DIAGNOSTIC ACCURACY OF NEUROIMAGING IN PEDIATRIC OPTIC PATHWAY/SELLAR/SUPRASELLAR TUMORS. Issue 2 (22nd June 2018) - Norris, Gregory; Garcia, Jacquelyn; Hankinson, Todd; Handler, Michael; Foreman, Nicholas; Mirsky, David; Stence, Nicholas; Dorris, Kathleen; Green, Adam
Abstract: INTRODUCTION: Various tumors arising in the optic pathway/sellar/suprasellar region in children necessitate different therapeutic approaches. Although surgical biopsy is the gold standard for diagnosis, not all tumors in this area require surgical intervention, and surgery here is associated with a high risk of morbidity. If an accurate diagnosis can be made by neuroimaging alone, surgery may be avoided completely for some tumors. We evaluated the ability to differentiate tumor type by neuroimaging in the optic pathway/sellar/suprasellar region. METHODS: 53 patients were identified at our institution from 2007-2017 who were diagnosed with optic pathway glioma (OPG), craniopharyngioma, germ cell tumor (GCT), or Langerhans cell histiocytosis (LCH) of the optic pathway/sellar/suprasellar region by biopsy. Patients with neurofibromatosis type 1 were excluded, as their tumors in this area are presumed to be OPG. We compared the predicted diagnosis from the neuroimaging (MRI/CT) read(s) to the pathologic diagnosis. RESULTS: 38 of 53 tumors were correctly diagnosed by neuroimaging, for a prediction accuracy of 72%. The prediction accuracies were for 87% (20/23) for craniopharyngioma, 79% (11/14) for OPG, 64% (7/11) for GCT, and 0% (0/5) for LCH. CT to look for calcifications was helpful in diagnosing craniopharyngioma. Presence of a posterior pituitary bright spot excluded GCT and LCH. CONCLUSIONS: Diagnosis of pediatric tumors in the optic pathway/sellar/suprasellar region by imaging alone should be considered when biopsy is considered high-risk. CT is indicated if craniopharyngioma is in the differential. Biopsy is needed to differentiate GCT from LCH when the posterior pituitary bright spot is absent.